Analysis of the developmental trends of results of hammer throwers in Croatia from 2008 to 2020: original scientific paper - Štekovic, K.; Strukar, S. (Homosporticus, 2021)
The goal of this research is to determine direction in which these results are heading for both, women and men, in throwing events in Croatia, as well as to recognize the possible factors which have influenced the defined direction in analyzed results. The sample of examines includes all Croatian hammer throwers (N=130) who were ranked in the top 10 in season standings from 2008 to 2020. Research variables were results of male and female hammer throwers. Polynomial regression analysis of 2nd and 3rd degree was used as a primary statistic method to define development direction and result prediction. Development directions of results differ based on gender. Development trends of results in men follow negative direction, while in women they follow positive direction. Prognosis of women indicates high-level results where the best seasonal result reaches entry standard for World Athletics Championships in Oregon 2022 (=72,50m). Average score prognosis of the first 3 seasonal results were close to national entry standard for athletes II. category (=69,00m), while average score prognosis of the first 10 results were close to entry standard for athletes III. category (=57,00m). Prognosis of men show very low value where the best seasonal result was at III. category level. Possible positive effect factors on results: quality coaching based on scientific methods. Possible negative effect factors on results: young throwers population, inadequate investing in hammer throw event or non-existing national role model who would encourage young athletes to start hammer throw training.